Aperture coupled perturbed antenna with a parasitic element for rapidly deployable wireless ATM network - Esa, Mazlina; Noor, N. A. M.; Hamid, M. R.; Subahir, Suhaila; Fisal, Norsheila; Yusof, Sharifah Kamilah (ieee, 2000)

(untitled)
A circular perturbed patch antenna with an aperture coupling feed and has a parasitic element of the same patch shape is presented. The antenna is proposed for the receiver of a rapidly deployable wireless ATM (asynchronous transfer mode) network, operating at 1.57542 GHz. The receiver is able to receive the signal beamed by the Global Positioning System (GPS) satellite which carries the navigation message. The basis of the antenna is a circular patch which is then perturbed to achieve circular polarisation which matches the GPS signal. The aperture coupling feed has the advantage of avoiding physical connection to the antenna radiating structure. A shunt quarter-wavelength open-circuited stub was employed with the microstrip feed to reduce unneeded back radiation. This enhances the relative gain of the broad beamwidth broadside radiating antenna. The antenna was experimentally found to be well matched at the frequency of operation and exhibit a sufficient 3% reflection bandwidth